2020
DOI: 10.1111/jfb.14234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on aerobic metabolism and active electrosensory acquisition in the African weakly electric fish Marcusenius victoriae

Abstract: Environmental hypoxia has effected numerous and well-documented anatomical, physiological and behavioural adaptations in fishes. Comparatively little is known about hypoxia's impacts on sensing because it is difficult to quantify sensory acquisition in vivo. Weakly electric fishes, however, rely heavily on an easily-measurable sensory modality-active electric sensing-whereby individuals emit and detect electric organ discharges (EODs). In this study, hypoxia tolerance of a mormyrid weakly electric fish, Marcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…These fishes are protected from predation by Nile perch, as this species does not penetrate the dense swamp and is sensitive to hypoxia (Chapman et al, 2002). Inundation levels, water temperature and DO in the wetland show seasonal and diel variation, though DO remains generally low (previously reported diurnal ranges: 1.06-2.63 mg O 2 L-1, Reardon and Chapman, 2008; 0.69-0.82 mg O 2 L-1, Moulton et al, 2020), and water conductivity is very low (10-20 µS cm 1 , measured manually during sampling). All research conducted in Uganda was approved by the Uganda National Council for Science and Technology (research clearance nr.…”
Section: Study Sitementioning
confidence: 96%
See 2 more Smart Citations
“…These fishes are protected from predation by Nile perch, as this species does not penetrate the dense swamp and is sensitive to hypoxia (Chapman et al, 2002). Inundation levels, water temperature and DO in the wetland show seasonal and diel variation, though DO remains generally low (previously reported diurnal ranges: 1.06-2.63 mg O 2 L-1, Reardon and Chapman, 2008; 0.69-0.82 mg O 2 L-1, Moulton et al, 2020), and water conductivity is very low (10-20 µS cm 1 , measured manually during sampling). All research conducted in Uganda was approved by the Uganda National Council for Science and Technology (research clearance nr.…”
Section: Study Sitementioning
confidence: 96%
“…The lake is surrounded by an extensive wetland area (Lwamunda Swamp), which is dominated by the emergent grass Miscanthidium violaceum that transitions to water lilies (Nymphaea lotus and N. carulea) or hippo grass (Vossia cuspidata) at the lake edge (Chapman et al, 1996a;Chrétien and Chapman, 2016). Various fish species occur deep within the wetland (see species list in Chapman et al, 1996b), including P. degeni and M. victoriae (Chapman et al, 1996b(Chapman et al, , 2002Chapman and Hulen, 2001;Moulton et al, 2020). These fishes are protected from predation by Nile perch, as this species does not penetrate the dense swamp and is sensitive to hypoxia (Chapman et al, 2002).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Fish adapt to hypoxia stress through a series of complex physiological and biochemical processes, including a reduction in the metabolic rate, changes in metabolic pathways, and an improvement in the oxygen transport capacity [9,10]. Many studies have found that when an organism is in an anoxic environment, glycolipid metabolism undergoes a series of changes [11][12][13][14]. Anaerobic metabolism can reduce oxygen consumption and quickly provide energy under hypoxia stress [15].…”
Section: Introductionmentioning
confidence: 99%
“…Their EODs are easy to measure, which makes them particularly well suited to research on the energetics of sensation and communication (e.g. Julian et al, 2003;Markham et al, 2016;Moulton et al, 2020;Reardon et al, 2011;Salazar et al, 2013).…”
mentioning
confidence: 99%